INTEGRATION OF SCHOOL ADMINISTRATION SYSTEM AND ACADEMIC SUPERVISION AS AN EFFORTS TO IMPROVE THE QUALITY OF EDUCATION - Sandyawati, Novi Sri; MS, Rudy Handoko; SU, Arif Darmawan (International Journal of Multidisciplinary Research and Literature, 2022)
In the implementation of school education, the education administration system has a function that determines the form, structure and content of school program planning; arrangements and management, and an appropriate organizational plan and coordination system for school activities to run effectively towards the vision of education. This study aims to provide an overview of the administration and academic supervision programs in vocational high schools that should be integrated. The qualitative research method was designed through a case study approach, the CIPP (Context, Input, Process and Product) model, designed through a checklist as a guide for researchers. The study results illustrate that the education administration as a governance system to integrate all resources related to the effectiveness of the learning process for improving the quality or achieving educational goals has not shown significant changes. Implementing academic supervision has not been integrated with the school administration system, which can be seen from the scheduling. It is carried out once every semester, outside the supervision task's provisions where teachers should receive supervision at least twice in one semester. In addition, teachers face several problems related to the teaching and learning process that require supervision assistance. This illustrates that the supervision program has a continuous sequence